KETERAMPILAN MENGAJAR CALON GURU SD DI SD SANTO PETRUS MEDAN - Patri Janson Silaban; Elda Syekiah Simamora; Dea Melani Br. Ginting; Elda Rasinta Sipayung; Sally Mayke Lumba Batu; Winda Adisty Br. Ginting; Artika Barus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to evaluate the teaching skills of prospective elementary school teachers at Santo Petrus Elementary School Medan through an approach that includes data collection techniques in the form of questionnaires, observations, and interviews. The assessment of teaching skills includes preliminary, core, and closing activities in learning, which are associated with learning theories from experts such as John Dewey, Abraham Maslow, Robert Gagné, Piaget, Vygotsky, Bruner, and others. The results of the study showed that the teaching skills of six prospective teachers had an average score of 91.97, with several superior aspects, such as student motivation and mastery of the material. However, several areas such as the use of learning media and student interaction still need improvement. This study emphasizes the importance of applying modern learning theories to create a more holistic and meaningful learning experience for students.